2014
DOI: 10.1007/s12015-014-9551-y
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-Derived Mesenchymal Stem Cells Improve Motor Functions and are Neuroprotective in the 6-Hydroxydopamine-Rat Model for Parkinson’s Disease when Cultured in Monolayer Cultures but Suppress Hippocampal Neurogenesis and Hippocampal Memory Function when Cultured in Spheroids

Abstract: Adult human adipose-derived mesenchymal stem cells (MSC) have been reported to induce neuroprotective effects in models for Parkinson's disease (PD). However, these effects strongly depend on the most optimal application of the transplant. In the present study we compared monolayer-cultured (aMSC) and spheroid (sMSC) MSC following transplantation into the substantia nigra (SN) of 6-OHDA lesioned rats regarding effects on the local microenvironment, degeneration of dopaminergic neurons, neurogenesis in the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 81 publications
7
38
0
Order By: Relevance
“…Furthermore, neuronal loss in the OB showed a strong correlation with disease duration in PD [5], implicating a progressive degeneration of OB neurons. Furthermore, our colleagues showed a profound effect of AD-MSC on TH and BDNF levels and on motor behavior in Parkinsonian rats [27]. In line with previous studies [4], we found a positive correlation between the amount of subventricular BrdU+/ HuD+ neurons and the amount of dopaminergic neurons in all groups, indicating a relationship of increased neurogenesis with increased dopaminergic tone.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, neuronal loss in the OB showed a strong correlation with disease duration in PD [5], implicating a progressive degeneration of OB neurons. Furthermore, our colleagues showed a profound effect of AD-MSC on TH and BDNF levels and on motor behavior in Parkinsonian rats [27]. In line with previous studies [4], we found a positive correlation between the amount of subventricular BrdU+/ HuD+ neurons and the amount of dopaminergic neurons in all groups, indicating a relationship of increased neurogenesis with increased dopaminergic tone.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, stem cells have been proposed as a promising tool to achieve neurorestoration in the PD brain. Numerous studies have been conducted in PD animal models, with different stem cell types, including embryonic [5][6][7] or adult neural stem cells [8], dopaminergic cells differentiated from fibroblast-derived inducible pluripotent stem (iPS) cells [9][10][11] and bone marrow-and adiposederived mesenchymal stem cells (MSCs) [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of MSCs as an effective PD treatment is still controversial because MSCs can both stimulate and inhibit the immune system (Dazzi et al, 2012;English & Mahon, 2011;Yagi et al, 2010). In fact, some authors have demonstrated a neuroprotective effect of these cells in vitro and in vivo (Ooi, Dheen, & Tay, 2015;Schwerk et al, 2015;Stemberger et al, 2011;F. Wang et al, 2010), but other authors could not demonstrate it (Camp, Loeffler, Farrah, Borneman, & LeWitt, 2009;Eliopoulos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%